2022
DOI: 10.1038/s41598-022-10036-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental modelling studies on the removal of dyes and heavy metal ions using ZnFe2O4 nanoparticles

Abstract: The presence of dyes and heavy metals in water sources as pollutants is harmful to human and animal health. Therefore, this study aimed to evaluate the efficacy of zinc ferrite (ZnFe2O4) nanoparticles (ZF-NPs) due to their outstanding properties including cost-effectiveness, availability, and applicability for removal of auramine O (AO), methylene blue (MB), and Cd (II). The effect of the main operating parameters such as AO concentration, MB concentration, Cd (II) concentration, adsorbent amount, solution pH,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 54 publications
(43 reference statements)
1
5
0
1
Order By: Relevance
“…The significance of each term in the quadratic model is determined by the model F and P- values 42 . In general, a higher F-value and lower P-value of a variable revealed the significance of the model terms 43 . According to the ANOVA results, the F-value for removing Cd(II) is 124.57 implies the model is statistically significant.…”
Section: Resultsmentioning
confidence: 97%
“…The significance of each term in the quadratic model is determined by the model F and P- values 42 . In general, a higher F-value and lower P-value of a variable revealed the significance of the model terms 43 . According to the ANOVA results, the F-value for removing Cd(II) is 124.57 implies the model is statistically significant.…”
Section: Resultsmentioning
confidence: 97%
“…The rate-determining step is assumed to be chemisorption in the pseudo-second-order model, including valence forces by exchanging or sharing adsorbate and adsorbent electrons. In addition, the adsorption capacity is proportional to the number of active sites involved on the adsorbent surface 8 , 63 . Therefore, it can be concluded that the adsorption of Pb 2+ ions on to Pip@MGO nanocomposite is mostly the chemical reactive adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…Concentration of the dye solution was determined using absorbance value of solution before and after contact with the adsorbent dose. The studies performed were of contact time, initial dye concentration, pH, temperature and adsorbent dose [14][15][16][17][18].…”
Section: Batch Adsorption Experimentsmentioning
confidence: 99%